ANALISIS DEPENDENSI PERBANKAN DAN PASAR MODAL SERTA PENGARUHNYA TERHADAP KINERJA PERUSAHAAN TERBUKA PADA SEKTOR PROPERTI DI INDONESIA - Elmizan, Gina Hafieza; idris, Idris; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2014)
This article focused on analyzing (1) the influence of banking transaction cost, moral hazard, adverse selection, and externality cost toward the banking dependency of public property companies in Indonesia; (2) the influence of capital market transaction cost, moral hazard, adverse selection, and externality cost toward the capital market dependency of public property companies in Indonesia; (3) the influence of banking dependency, capital market dependency, construction cost, marketing cost, credit interest rate, national economy and inflation rate toward the performance of public property companies in Indonesia; and (4) the prospects of the banking dependency, capital market dependency, and performance of public property companies in Indonesia. The data used is a panel data with 45 observations (15 companies during 2010-2012). This article uses Common Effect Model Regression to answer all research questions. The research concludes that (1) banking transaction cost, moral hazard, adverse selection, and externality cost do not significantly influence the banking dependency of public property companies in Indonesia, with adjusted R-squared of 17,57%; (2) capital market transaction cost, moral hazard, adverse selection, and externality cost significantly influence the capital market dependency of public property companies in Indonesia, with adjusted R-squared of 50,00%; (3) banking dependency, capital market dependency, construction cost, marketing cost, credit interest rate, national economy and inflation rate significantly influence the performance of public property companies in Indonesia, with adjusted R-squared of 28,46%; and (4) the banking dependency and performance of the companies tend to slow down in 2013-2015, while the capital market dependency tends to slightly grow. Keywords : Property Performance, Banking Dependency, Capital Market Dependency.